2016
DOI: 10.9790/3008-1104032023
|View full text |Cite
|
Sign up to set email alerts
|

Anatomical Variations of the Paranasal Sinuses In Chronic Rhinosinusitis

Abstract: Abstract:Chronic rhinosinusitis (CRS), an extremely persistent illness, is surgically best treated by

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…In study done by [6], the most prevalent variation found was septal deviation (63%). Septal deviation plays an important role in causing sinusitis and complications during endoscopic sinus surgery.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations
“…In study done by [6], the most prevalent variation found was septal deviation (63%). Septal deviation plays an important role in causing sinusitis and complications during endoscopic sinus surgery.…”
Section: Discussionmentioning
confidence: 98%
“…It is found that men may potentially suffers more from chronic rhinosinusitis than women, possibly because the different activities done by men and women, where men mostly spend their time outdoor, thus more prone to pollution, dust, cold air, and dry air that cause disruption of mucociliaary clearance [6].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations